A comparative study on the fashion design process utilizing shape memory textiles and conventional textiles: implications for the industry and education - Shin Young Jang; Chahong Chung; Jisoo Ha (Fashion and Textiles)
Abstract This study compares fashion design processes involving shape memory textiles (SMTs) compared to ones involving conventional textiles (CTs). The primary objectives were to identify barriers to the adoption of SMTs in the fashion industry from designers' perspectives, assess the impact of SMTs on conventional design processes, and develop strategies to enhance the use of SMTs in fashion design. Data collection involved three phases: design tasks using CTs, design tasks using SMTs, and in-depth interviews with 22 fashion design professionals. Findings revealed that designers typically followed a sequential process for both conventional and SMTs, starting with gathering references, sketching, and creating technical drawings. However, while concurrent reference gathering and sketching were common in CTs, for SMTs, additional research stages were required due to uncertainties in materials and challenges in keyword searches. Designers often shifted focus from trend-centric design to exploring functional possibilities with SMTs, potentially leading to fewer trendy designs. Major challenges included defining and classifying smart textiles including SMTs, visualizing shape-changing properties, and a lack of practical experience with these innovative materials. The insights form a guideline for collaborative efforts among manufacturing, design, and educational sectors to ensure that SMTs are integrated into the fashion industry.